Penggunaan Usability Testing Sebagai Metode Evaluasi Website E-Learning Universitas Teknologi Yogyakarta - Puspita, Naqiyyah Tasya (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2024)
E-Learning UTY has been developed using one of the popular Open Source LMS platforms, namely Moodle. The purpose of developing E-Learning UTY is to provide supporting facilities in the academic process. This study aims to assess the usability level of the E-Learning UTY website using the SUS method. The study involved 26 respondents, and a SUS score of 76.4 was obtained. This score places the E-Learning UTY website in the grade category of B+, indicating a good and acceptable adjective rating. However, users are not yet able to recommend the E-Learning UTY website to others as they are still in the passive user stage rather than being promoters. To enhance user experience, improvements are needed, especially in the interface of the E-Learning UTY website to make it more user-friendly and improve the usability of its features. Overall, the E-Learning UTY website has provided satisfactory user satisfaction.